Tradisi Mapparola pada Masyarakat Bugis di Kelurahan Wawotobi Kabupaten Konawe - Musfira; La Niampe; Nurtikawati; Wa Kuasa Baka (Jurusan Tradisi Lisan, Fakultas Ilmu Budaya, Univeritas Halu Oleo, 2023)
This study aims to answer the formulation of the problem, namely how the process and function of the Mapparola tradition in the Bugis community in the Wawotobi Village, Konawe Regency by analyzing and describing the data on these traditions. The mapparola tradition is one of a series of processions in Bugis wedding customs which are carried out after the ceremony. The method used in this research is a qualitative research method. Data collection was carried out using observation techniques, in-depth interviews and document studies. The informant determination technique in this study was carried out by purposive sampling. The data analysis technique uses three stages, namely (1) data reduction; (2) data display (data display); (3) drawing conclusions/verification (conclusion drawing/verifwing). The results of this study indicate that the Mapparola procession of carrying out the Mapparola tradition is still carried out with stages of implementation that have been passed down from generation to generation. While the functions contained in the tradition include; The Whole Functioning (stating the function of mapparola as the integration of the entire tribe community), Function of the System (functioning of the unity of political, cultural, economic systems, etc.), and Sociological and biological functions (cultural preservation not only on biological heritage, but Mapparola's sociological heritage as well very influential).